APLIKASI PENCATATAN PENJUALAN PENGDINGIN RUANGAN BERBASIS JAVA PADA PT. UNIE SARANA MANDIRI - Ispandi; Ramadan, Rino; Atmaja, Rahdian Kusuma (Universitas Lancang Kuning, 2024)
Unie Sarana Mandiri is a company engaged in the sale, installation and routine maintenance of air conditioners, therefore, sales and data collection units for air conditioners still use the manual method, so there are often difficulties in finding data, collecting data on goods, transactions and making reports, all of which are still recorded. in Ms. Excel and Ms. Offices. The method used in this research is the Waterfall method. For this reason, the researcher designed an application using NeatBeans. The design of this sales application is in the form of a desktop by presenting data collection of goods and sales reports. This application is designed using Neatbeans which is a support program for creating Java-based applications using Black Box in testing. Java-based air conditioner sales applications have had good performance, efficiency, application suitability with testing. This application can help employee performance in sales report item data by utilizing information technology to complement existing deficiencies in air conditioning sales, as media and information at PT. Unie Sarana Mandiri.